Social representations about the causes of accidents with needlestick materials by nursing technicians - Lubenow, Juliana Almeida Marques (2012)
The accidents with needlestick materials are serious due to the diseases that can be caused. This is a descriptive study with qualitative approach and it was developed at a private hospital in Piauí, Brazil, between March and June 2011. The objective is analyzing the causes attributed by nursing technicians to their own accidents with needlestick, using the Social Representations Theory. Deep interviews were applied to 16 professionals who suffered this kind of accident. Data were processed in the ALCESTE 4.8 software, which evidenced lack of care as the main cause identified by them. They also pointed out work colleague’s negligence and patient’s agitation. The prevailing social representation is that the accident only occurs because of professional’s irresponsible behavior. It can be concluded, however, that each percutaneous exposition must be individually analyzed in the search of real causes which do not only blame the worker.